Corruption Breeds Corruption. (June 2014) - Ghatak, Anirban; Iyengar, Sudarshan
We study extortion bribe or harassment bribe as a mode of corruption in this article. Corruption is modelled as a network game in the study. We take reputation into account in this model, and assume that reputation has a direct effect on the pay-offs of the agents in this game. We find the necessary conditions to make corruption as an Evolutionarily Stable Strategy against Multiple Mutations (ESSMM) in a game where players have both corruption and honesty as their strategies. ESSMM posits itself as a better tool than Evolutionarily Stable Strategy (ESS) to analyze such a situation where a society strives to eradicate traits like corruption completely. We claim that in a market norm (Ariely, 2013) oriented society, corruption breeds corruption and infects the whole society through robust asexual reproduction.